Venetoclax plus cyclophosphamide and cytarabine as induction regimen for adult acute myeloid leukemia - Zhang, Baohang; Liu, Qingguo; Li, Junfan; Hu, Yimin; Zhao, Xin; Huang, Pingping; Li, Shangzhu; Wang, Ying (Frontiers in Oncology, 2023)
The efficacy of induction chemotherapy (IC) for acute myeloid leukemia (AML) has improved significantly with the application of targeting drugs. Our previous study showed that 4-day IC regimen of cyclophosphamide (CTX) and Ara-C (CA （4+3）) achieved similar complete remission (CR) rate （80%） compared to traditional 7-day regimen, and survival rate appeared to be better. In this pilot study, we further shortened CA regimen to 3 days and added low-dose venetoclax (VEN, 200mg/day) (VCA) and reported the efficacy and safety here. Twenty-five newly diagnosed adult AML patients were enrolled in this study and evaluated for the remission rate after one-cycle VCA regimen. The CR/CRi was 92%, and all these patients had undetectable minimal residual disease (MRD-). The overall survival at 12 months was 79.3%. Median time to platelet recovery and absolute neutrophil count recovery both were 16 days, faster than that of traditional IC. In conclusion, this study showed that the 3-day CTX and Ara-C regimen is highly effective in newly diagnosed AML patients, and addition of VEN to CA regimen achieves higher and deeper one-course remission.